Cytoplasmic Domain of Sendai Virus HN Protein Contains a Specific Sequence Required for Its Incorporation into Virions - Takimoto, Toru (American Society for Microbiology, 1998)
In the assembly of paramyxoviruses, interactions between viral proteins are presumed to be specific. The focus of this study is to elucidate the protein-protein interactions during the final stage of viral assembly that result in the incorporation of the viral envelope proteins into virions. To this end, we examined the specificity of HN incorporation into progeny virions by transiently transfecting HN cDNA genes into Sendai virus (SV)-infected cells. SV HN expressed from cDNA was efficiently incorporated into progeny Sendai virions, whereas Newcastle disease virus (NDV) HN was not. This observation supports the theory of a selective mechanism for HN incorporation. To identify the region on HN responsible for the selective incorporation, we constructed chimeric SV and NDV HN cDNAs and evaluated the incorporation of expressed proteins into progeny virions. Chimera HN that contained the SV cytoplasmic domain fused to the transmembrane and external domains of the NDV HN was incorporated to SV particles, indicating that amino acids in the cytoplasmic domain are responsible for the observed specificity. Additional experiments using the chimeric HNs showed that 14 N-terminal amino acids are sufficient for the specificity. Further analysis identified five consecutive amino acids (residues 10 to 14) that were required for the specific incorporation of HN into SV. These residues are conserved among all strains of SV as well as those of its counterpart, human parainfluenza virus type 1. These results suggest that this region near the N terminus of HN interacts with another viral protein(s) to lead to the specific incorporation of HN into progeny virions.